2013
DOI: 10.1007/s00404-013-2813-0
|View full text |Cite
|
Sign up to set email alerts
|

Role of endometrial power Doppler ultrasound using the international endometrial tumor analysis group classification in predicting intrauterine pathology

Abstract: The nomenclature described by IETA group for power Doppler assessment of the endometrium is clinically valuable and reasonable. Using this terminology, it will be easier to compare results of different studies on endometrial Doppler sonography in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…Endometrial hyperplasia was more frequently assigned a color score of 2. Certainly, as did Kabul Kucur et al, we found that virtually all cases of myoma (only 3 cases, in fact) were assigned a color score of 3 of 4 by all examiners.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Endometrial hyperplasia was more frequently assigned a color score of 2. Certainly, as did Kabul Kucur et al, we found that virtually all cases of myoma (only 3 cases, in fact) were assigned a color score of 3 of 4 by all examiners.…”
Section: Discussionsupporting
confidence: 62%
“…One single study prospectively evaluated the power Doppler criteria proposed by the IETA group for assessing endometrial vascularization in women with suspected endometrial disorders. Kabil Kucur et al evaluated 97 women with clinical suspicion of endometrial lesions. Histologically, of the 97 women, 39 had endometrial polyps; 9 had endometrial hyperplasia; 10 had submucous myoma; 7 had endometrial cancer; and 32 had “other nonspecific pathologies.” They did not find statistically significant differences in the color score among different pathologic types.…”
Section: Discussionmentioning
confidence: 99%
“…It allows the evaluation of the number, size, echogenicity of the myomas, as well as the detection of any comorbidities (whether uterine or adnexal); the use of color Doppler and power Doppler modalities allows to analyze the vascularization of the masses (27). Moreover, TVUS provides the parameter of myometrial-free margin (MFM: the thickness of myometrium between the deepest pole and the perimeter of the myoma) (28), that delivers a safety margin for hysteroscopic-guided surgical maneuvers and aims at preventing the risk of perforation.…”
Section: Scientific Evidencementioning
confidence: 99%
“…Therefore, the International Endometrial Tumor Analysis (IETA) group published a consensus opinion in 2010 on the terms, definitions and measurements of the endometrium 16 . Using the IETA terminology, the most commonly reported features of EC are endometrium with heterogeneous echogenicity, irregular or ill‐defined endometrial‐myometrial junction and multiple vessels with focal or multifocal origin on Doppler ultrasound 17–20 . Assessment of the presence of these ultrasound features, in addition to measurement of ET, may improve the diagnosis of EC.…”
Section: Introductionmentioning
confidence: 99%